2019
DOI: 10.1039/c8mo00139a
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the intracellular effects of hyperbranched polycation–DNA complexes on lung cancer cells using LC-MS-based metabolite profiling

Abstract: A metabolomics approach is used to assess the molecular mechanisms underlying the effects of polycation gene delivery vectors on lung cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…2). Six replicates were deemed to be valid for this type of cell linebased studies (Alazzo et al 2019;Surrati et al 2016). This separation indicated a distinctive metabolic signature of M1, M2 and M0 macrophages.…”
Section: Feature Selection and Identification Of Potential Biomarker mentioning
confidence: 99%
“…2). Six replicates were deemed to be valid for this type of cell linebased studies (Alazzo et al 2019;Surrati et al 2016). This separation indicated a distinctive metabolic signature of M1, M2 and M0 macrophages.…”
Section: Feature Selection and Identification Of Potential Biomarker mentioning
confidence: 99%
“…A correlation exists between toxicity and transfection efficiency (Alazzo et al, 2019) but this does not seem to be the case with sugar-functionalized PLL synergistic compounds (Han et al, 2018), which showed great affinity for loading siRNA, less cytotoxicity and maintained transfection efficiency as the original PLL modified by stearylamine. Surprisingly, it could even knock down some disease-related genes.…”
Section: Adjuvants Of Gene Therapymentioning
confidence: 97%
“…Meanwhile, as a dense group of distribution exists outside, LBD carriers protect the loaded ribonucleic acid from immune responses and nuclease degradation (Han et al, 2018). This non-viral system shows many advantages, including higher loading capacity, less inflammation potential, lower insertion mutagenic induction potential, cheaper scale, and easier functionalization, than the viral system (Walsh et al, 2018;Alazzo et al, 2019;Gorzkiewicz et al, 2020a). All these advantages make this non-viral system attract increasing attention.…”
Section: Adjuvants Of Gene Therapymentioning
confidence: 99%
See 2 more Smart Citations